Communication skills and social interaction in university students from Lima - Guillén-Chávez, Sergio Raúl (2021)
The present study aims to establish the correlation between communication skills and social interaction among students of the Faculty of Education of a public university in Lima. The research is framed under the positivist paradigm, with a quantitative approach, a basic type, of the non-experimental design, with a cross section, of the sub-type of correlational design. The population was census, consisting of 214 students, who were administered two valid and reliable questionnaires: the communication skills instrument (ratified by KR-20 = 0.98) and social interaction (validated by Cronbach's Alpha = 0.988). The results showing the existence of a significant and direct link between communication skills and social interaction (Spearman's Rho =, 823). Finally, it was concluded that, if students develop communication skills such as reception, emission, handling of non-verbal communication, assertive then the social interaction of the students is strengthened.